INTERNALIZATION OF RELIGIOUS MODERATION VALUES IN HIGH SCHOOL BASED ON ISLAMIC BOARDING SCHOOLS - Badi' Rohmawati, Ulva; Izza, Yogi Prana (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2022)
Nowadays, there are so many sects or groups in the name of Islam. However, not all schools are by Islamic teachings. Adolescents who have not yet matured in their religious understanding or whose knowledge is still shallow will be easily tempted to follow various sects. So that, radicalism is very easy to spread among teenagers. Education in Islamic boarding schools emphasizes the teaching of religious knowledge. It is supposed to teach the values of religious moderation to teenagers. It is essential to teach the values of religious moderation to teenagers whose age is if the formal school is at the high school level. This study aims to analyze and examine the process of internalizing the values of religious moderation in pesantren-based schools. This research was conducted at SMA Plus Al-Fatimah, located at Jl. Pondok Bambu No.01 Sukorejo Bojonegoro. This study uses a qualitative approach and the type of case study. Data analysis techniques are in the form of data reduction, data display, and description or conclusions. The survey results in instilling the values of religious moderation in pesantren-based schools were carried out by first, the process of internalizing the importance of religious moderation in pesantren-based schools, and secondly, the characteristics of students' religious moderation. The implications obtained can instill various moderating values in students, instilling and implementing the good values exemplified by the Prophet Muhammad SAW.